Kompetensi Manajerial Kepala Sekolah dalam Pengelolaan Sarana Prasarana terhadap Peningkatan Kualitas Pendidikan - Rumsanah, Rumsanah; Nugraha, Enung; Firdaos, Rijal; Zohriah, Anis; Mu’in, Abdul (Universitas Sarjanawiyata Tamansiswa, 2025)
Quality education requires the support of effective school management, particularly through the principal's managerial competence in managing facilities and infrastructure. Well-planned facilities and infrastructure are believed to create a conducive learning environment that influences the quality of learning. This study aims to explore the role of principals' managerial competence in planning, organizing, and supervising educational facilities and infrastructure in Islamic Elementary Schools (Madrasah Ibtidaiyah) as an effort to improve the quality of education. The method used was a qualitative case study approach at MI Attamam and MI Daarul Ilmi in Tangerang Regency, Banten. Data were collected through interviews, observations, and document analysis, then analyzed thematically. The results show that principals play a central role in ensuring the availability, utilization, and maintenance of facilities and infrastructure. Constraints such as budget limitations and school community participation were overcome through collaborative strategies, innovation, and a participatory management system. The novelty of this research lies in mapping the principals' managerial strategies in two madrasas with different conditions, as well as the direct link between infrastructure management and non-academic learning quality indicators. Practically, this research provides an alternative model for infrastructure management that is adaptive and applicable to madrasas. Theoretically, this research enriches the study of Islamic education management by emphasizing the principal's role as an innovator and driver of infrastructure-based educational quality.